Texts from Jane Eyre : and other conversations with your favorite literary characters - Lavery, Daniel M. (Henry Holt and Company, 2014)
"Hilariously imagined text conversations--the passive aggressive, the clever, and the strange--from classic and modern literary figures, from Scarlett O'Hara to Jessica Wakefield. Mallory Ortberg, the co-creator of the cult-favorite website The Toast, presents this whimsical collection of hysterical text conversations from your favorite literary characters. Everyone knows that if Scarlett O'Hara had an unlimited text-and-data plan, she'd constantly try to tempt Ashley away from Melanie with suggestive messages. If Mr. Rochester could text Jane Eyre, his ardent missives would obviously be in all-caps. And Daisy Buchanan would not only text while driving, she'd text you to pick her up after she totaled her car. Based on the popular web-feature, Texts from Jane Eyre is a witty, irreverent mashup that brings the characters from your favorite books into the twenty-first century"--